REACH FOR STARS (Author: Ouida Wright) - Catterson, J. (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1967)
Ouida Wright, ed. Reach for Stars, Toronto: Ginn and Company, 1966, Reader and Teachers' Manual, 480 pp. and vi, 351 pp.